Assessment of the level of digital maturity of the national tax administration system - E. O. Balaev (Вестник Северо-Кавказского федерального университета)
Introduction. There is a need to improve the efficiency of tax administration in the dynamically developing digital world. Digital maturity models are an important tool for assessing the state of national tax administration systems and developing appropriate development strategies. The introduction of digital technologies in the tax sphere can significantly improve the interaction between government agencies and taxpayers, improve the quality of tax services and ensure more effective control over tax payments.Goal. To assess the level of digital maturity of the tax administration system of the Russian Federation. Materials and methods. The assessment will be carried out taking into account such factors as the development of tax control and monitoring tools, the availability of technological resources and the complexity of the tasks performed. To achieve this goal, qualitative and quantitative studies were used, including a study of regulatory documents, an analysis of existing digital maturity models and the practice of their application in tax administration. Results and discussion. The results of the study revealed that the Russian tax administration system has completed the digital transformation at the first level. Interaction between tax authorities and taxpayers is now carried out through online platforms and the website of the Federal Tax Service of Russia, which allows for access to up-to-date information and the provision of necessary services. However, the transition to the second level of digital maturity is almost complete only with some reservations, in particular, there is no possibility of analyzing electronic invoices in real time. To achieve full completion of digital transformation, it is necessary to implement advanced information and analytical tools, such as big data technologies, artificial intelligence and blockchain.Conclusion. The Russian tax administration system is confidently moving towards full digital transformation, but to achieve a higher level of maturity, further development of technological capabilities and implementation of advanced solutions are necessary. This will create conditions for more effective interaction with taxpayers and improving the quality of tax services, which will help improve the tax climate in the country.